Knockdown of platinum‐induced growth differentiation factor 15 abrogates p27‐mediated tumor growth delay in the chemoresistant ovarian cancer model A2780cis. (10th December 2014) - Meier, Julia C.; Haendler, Bernard; Seidel, Henrik; Groth, Philip; Adams, Robert; Ziegelbauer, Karl; Kreft, Bertolt; Beckmann, Georg; Sommer, Anette; Kopitz, Charlotte
Abstract Molecular mechanisms underlying the development of resistance to platinum‐based treatment in patients with ovarian cancer remain poorly understood. This is mainly due to the lack of appropriate in vivo models allowing the identification of resistance‐related factors. In this study, we used human whole‐genome microarrays and linear model analysis to identify potential resistance‐related genes by comparing the expression profiles of the parental human ovarian cancer model A2780 and its platinum‐resistant variant A2780cis before and after carboplatin treatment in vivo. Growth differentiation factor 15 (GDF15) was identified as one of five potential resistance‐related genes in the A2780cis tumor model. Although A2780‐bearing mice showed a strong carboplatin‐induced increase of GDF15 plasma levels, the basal higher GDF15 plasma levels of A2780cis‐bearing mice showed no further increase after short‐term or long‐term carboplatin treatment. This correlated with a decreased DNA damage response, enhanced AKT survival signaling and abrogated cell cycle arrest in the carboplatin‐treated A2780cis tumors. Furthermore, knockdown of GDF15 in A2780cis cells did not alter cell proliferation but enhanced cell migration and colony size in vitro. Interestingly, in vivo knockdown of GDF15 in the A2780cis model led to a basal‐enhanced tumor growth, but increased sensitivity to carboplatin treatment as compared to the control‐transduced A2780cis tumors. This was associated with larger necrotic areas, a lobular tumor structure and increased p53 and p16 expression of the carboplatin‐treated shGDF15‐A2780cis tumors. Furthermore, shRNA‐mediated GDF15 knockdown abrogated p27 expression as compared to control‐transduced A2780cis tumors. In conclusion, these data show that GDF15 may contribute to carboplatin resistance by suppressing tumor growth through p27. These data show that GDF15 might serve as a novel treatment target in women with platinum‐resistant ovarian cancer.